You drive 6.0 km at 50 km/h and then another 6.0 km at 90 km/h. Your average speed over the 12 km drive will be _________

Answers

Answer 1
Answer:

Answer:

64.29\ (km)/(h)

Step-by-step explanation:

hello

the  speed is the relation between a distance traveled and the time used for it and it is given by the equation

v =(displacement)/(time)\n (1)v=(d)/(t)

Now, the average speed will be

v_(average) =(displacement\ total)/(total\ time)\n (1)v=(d)/(t) \n(2)v_(average)=(d_(t) )/(t_(t) )

Step 1

I drive 6.0 km at 50 km/h

from (1) it is possible to isolate t

(1)v=(d)/(t)\nt=(d)/(v)

Let

v=50 (km)/(h) \nd=6.0 km\nt=(d)/(v) \nt=(6.0 km)/(50 (km)/(h))\nt_(1)=0.12\ hours\n

Step 2

then I drive 6.0 km at 90 km/h

v=90 (km)/(h) \nd=6.0 km\nt=(d)/(v) \nt=(6.0 km)/(90 (km)/(h))\nt_(2)=0.067\ hours\n

Step 3

FInd total time and total displacement

Total\ time=t_(1) +t_(2) \nt_(t) =0.12\ hours +0.067\ hours =0.187\ hours\n\ntotal\ distance\ =d_(1) +d_(2)=6.0\ km +6.0\ km= 12\ km\n

step 4

finally, put these values into the equation(2)

v_(average)=(d_(t) )/(t_(t) )\nv_(average)=(12\ km )/(0.187\ h )\nv_(average)=64.29\ (km)/(h)

V=64.29 km/h

Have a good day

Answer 2
Answer:

Answer:

64.2857 km/h

Step-by-step explanation:

Time taken to drive the first 6.0 km in hours = 6/50

Time take to drive another 6.0 km in hours = 6/90

Total time taken to drive 12 km in hours = (6/50) + (6/90)

= 6(50+90)/50x90

= 6x140/50x90

= 840/4500

The average speed over the 12 km is therefore 12 divided by 840/4500

= (12 x4500)/840

= 64.2857 km/h


Related Questions

How do I solve this?24+3.1+(-44)+(-8.2)+63
What is the value of the expression? 19.2+(–7+3.8)a. 16b. 24c. 29d. 30
Explain why the following triangle cannot exist. Note that no angle measure are known.
-28=7(x-7) What does x=
Find the distance between the points (4, 4) and (-3, 5)

Three times the sum of a number and seven is two less than five times the number.

Answers

3 (x + 7) =  5x - 2
3x + 21 = 5x - 2
3x - 5x = -2 - 21

-2x = -23 
x = -23/-2
x = 23/2


Log2 + log(4x-1) = 3

Answers

remember
logx+logy=log(xy) so
log2+log(4x-1)=log2(4x-1)=log8x-1
since no base is mentioned, it it base 10


now we have
log 8x-2, base 10=3
means
10 must be raised to the 3rd power to get 8x-2
therfor
10^3=8x-2
1000=8x-2
1002=8x
divide 8 both sides
125.25=x


x=125.25

10^2.7=4x-1
(10^2.7+1)/4=x 
x=125.55

A satellite television company charges a one-time installation fee anda monthly service charge. The total cost is modeled by the function
y = 40 + 90x. Which statement represents the meaning of each part
of the function?
(1) y is the total cost, x is the number of months of service,
$90 is the installation fee, and $40 is the service charge per
month.
(2) y is the total cost, x is the number of months of service,
$40 is the installation fee, and $90 is the service charge per
month.
(3) x is the total cost, y is the number of months of service,
$40 is the installation fee, and $90 is the service charge per
month.
(4) x is the total cost, y is the number of months of service,
$90 is the installation fee, and $40 is the service charge per
month.

Answers

Answer:

Option (2).

Step-by-step explanation:

A satellite T.V. company charges one time installation fees along with monthly service charge.

Total cost is modeled by the function y = 40 + 90x

Here y = Total cost charged by the company

A one time installation charges = $40

Service charge for a month = $90

and number of months for which service was used = x months

Therefore, Option (2) explains the function well.

the answer is 2 y= total installation cost. x is the variable representing the number of months of service and $40 is the fixed price while $90 is dependent on the xvalue

What is 0.24 as a fraction in lowest terms

Answers

The only answer for 0.24 as a fraction is 6/25

Simplify the square root of 125

Answers

The value of the expression √125 will be 5√5.

We can first represent 125 as the product of its prime components in order to simplify the square root of that number. 5 x 5 x 5 is the prime factorization of 125. The quantity that, when multiplied by itself, equals 125 is known as the square root of 125. We may claim that the square root of 125 is 5√5, as 5 x 5 = 25, and 25 x 5 = 125.

Using the principle that the square root of a perfect square is the number itself, we may further reduce the square root of 125. Since 25 is a perfect square in this instance, its square root is just 5. Therefore, 5 √5 may also be used to represent the square root of 125.

More about the Algebra link is given below.

brainly.com/question/953809

#SPJ6

Hello,

as 125=5^3
√125=5√5

Helpppp i’ll give that crown thing

Answers

Answer:

N K Q

Step-by-step explanation: